FOLK TERMINOLOGY OF ARABLE FARMING IN THE RUSSIAN DIALECTS AND MICROTOPONYMY OF THE PERM REGION - Julija V. Zvereva (Philological Studies, 2019)
The article deals with geographical terms related to fieldwork. The analysis of the presented data indicates that in Permian dialects and microtoponymy of the Perm Krai the vocabulary of field cultivation is well preserved. A large number of words relating to ancient systems of farming, indicates a long-term preservation of archaic methods of cultivating land in the Perm Region. Geographical terms, analyzed in the article, show the connection between the vocabulary of Permian and North-Russian dialects and the interaction of Russian and Komi-Permian language in the territory of the Perm region.